Added Value of 3‐Dimensional Sonography for Endometrial Evaluation in Early Puerperium. (1st April 2013) - Weissmann-Brenner, Alina; Haas, Jigal; Barzilay, Eran; Gilboa, Yinon; Gat, Itai; Gindes, Liat; Mashiach, Roi; Achiron, Reuven; Dulitski, Mordechai
Abstract : Objectives: The purpose of this study was to examine the uterine cavity within 48 hours of delivery using 2‐ and 3‐dimensional sonography after normal vaginal deliveries, instrumental deliveries, exploration of the uterine cavity, and cesarean deliveries. Methods: A prospective study was performed in puerperal women with normal clinical examination findings. Measurements of the uterine length and width were taken in the midsagittal and coronal planes. Midsagittal measurements of the endometrium using 2‐ and 3‐dimensional sonography and virtual organ computer‐aided analysis were performed. Comparisons were made between normal and surgical vaginal deliveries, cesarean deliveries, and after exploration of the uterine cavity. Results: A total of 123 patients were examined. Seventy‐seven patients had normal vaginal deliveries; 21 had assisted vaginal deliveries; and 25 had cesarean deliveries. Thirteen underwent exploration of the uterine cavity. The uterine volume increased significantly as the birth weight increased and after cesarean delivery ( P < .05). No correlation was found between the endometrial volume and parity, birth weight, and mode of delivery, including no correlation with exploration. Five cases of placental residua were found in asymptomatic women. All delivered vaginally. None underwent exploration of the uterus. All had irregular echogenic masses in the uterine cavity with positive color Doppler findings. The endometrial thickness and volume were significantly higher in these patients. Conclusions: Sonography along with Doppler assessment has added value in the clinical evaluation of the puerperal women, being able to also show residua in asymptomatic women. Three‐dimensional sonography did not show an advantage over 2‐dimensional sonography in the estimation of the puerperal uterus or residua.